2012
DOI: 10.1016/j.neuron.2012.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Potentiates GluK3 Glutamate Receptor Function by Stabilizing the Ligand Binding Domain Dimer Interface

Abstract: SUMMARY Kainate receptors (KARs) play a key role in the regulation of synaptic networks. Here, we show that zinc, a cation released at a subset of glutamatergic synapses, potentiates glutamate currents mediated by homomeric and heteromeric KARs containing GluK3 at 10–100 μM concentrations, whereas it inhibits other KAR subtypes. Potentiation of GluK3 currents is mainly due to reduced desensitization, as shown by kinetic analysis and desensitization mutants. Crystallographic and mutation analyses revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 57 publications
(114 reference statements)
8
84
2
Order By: Relevance
“…, and Zn 2+ ions in vertebrate glutamate receptors (28)(29)(30)(31)(32), Mg 2+ stabilizes the LBD dimer assembly in ctenophores. Endogenous glycine is trapped in the ligand binding site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, and Zn 2+ ions in vertebrate glutamate receptors (28)(29)(30)(31)(32), Mg 2+ stabilizes the LBD dimer assembly in ctenophores. Endogenous glycine is trapped in the ligand binding site.…”
Section: Resultsmentioning
confidence: 99%
“…2A and Fig. S5 (31,32) and is generated by conserved amino acid substitutions unique to ctenophores (Fig. S6).…”
Section: Resultsmentioning
confidence: 99%
“…S6C). The cavity volume for GluRIIB is similar to that for GluA2 (218 Å 3 ), which binds both AMPA and kainate, as well as quisqualate (38,40), but smaller than that for GluK1, GluK2, and GluK3 volume 305, 255, and 299 Å 3 , respectively (39,41), suggesting that structural features unique to Drosophila NMJ iGluRs control ligand selectivity.…”
Section: Efficient Receptor Expression and Function Requires Multiplementioning
confidence: 92%
“…Since the surprising discovery that Zn 2+ is present in large amounts within synaptic vesicles in many areas of the brain (Maske, 1955), numerous studies have investigated the possible roles of this metal on synaptic function. These studies have revealed that synaptic Zn 2+ -- as an allosteric modulator -- inhibits GABA A , NMDA, and kainate receptors (Paoletti et al, 1997; Vogt et al, 2000; Ruiz et al, 2004; Mott et al, 2008; Nozaki et al, 2011; Veran et al, 2012), while potentiating glycine receptors (Hirzel et al, 2006). Moreover, synaptic Zn 2+ -- as a trigger of signaling pathways -- is thought to be required for mossy fiber long-term potentiation (LTP) via pre– and postsynaptic mechanisms (Huang et al, 2008; Pan et al, 2011); however, these results are not consistent with other studies suggesting that Zn 2+ signaling does not affect mossy fiber LTP (Vogt et al, 2000; Lavoie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%